The Collagen Repeat Sequence Is a Determinant of the Degree of Herpesvirus Saimiri STP Transforming Activity - Choi, Joong-Kook (American Society for Microbiology, 2000)
Herpesvirus saimiri (HVS) is divided into three subgroups, A, B, and C, based on sequence divergence at the left end of genomic DNA in which the saimiri transforming protein (STP) resides. Subgroup A and C strains transform primary common marmoset lymphocytes to interleukin-2-independent growth, whereas subgroup B strains do not. To investigate the nononcogenic phenotype of the subgroup B viruses, STP genes from seven subgroup B virus isolates were cloned and sequenced. Consistent with the lack of oncogenic activity of HVS subgroup B viruses, STP-B was deficient for transforming activity in rodent fibroblast cells. Sequence comparison reveals that STP-B lacks the signal-transducing modules found in STP proteins of the other subgroups, collagen repeats and an authentic SH2 binding motif. Substitution mutations demonstrated that the lack of collagen repeats but not an SH2 binding motif contributed to the nontransforming phenotype of STP-B. Introduction of the collagen repeat sequence induced oligomerization of STP-B, resulting in activation of NF-κB activity and deregulation of cell growth control. These results demonstrate that the collagen repeat sequence is a determinant of the degree of HVS STP transforming activity.